2020
DOI: 10.1111/jocn.15445
|View full text |Cite
|
Sign up to set email alerts
|

Dementia caregivers training needs and preferences for online interventions: A mixed‐methods study

Abstract: Aim To explore how informal caregivers of persons with dementia perceive training needs and preferences in the context of online training and support interventions. Background Informal dementia caregivers commonly present high needs across several domains. Paradoxically, they are more likely to have unmet needs and lower levels of service usage when compared to other caregivers. Most studies on unmet needs of dementia caregivers have been quantitative and resorted to assessment checklists, with a minority focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Concerning interaction with professionals in online interventions, participants in this study were perhaps more hesitant than what is usually reported in the literature ( Klein and Cook, 2010 ). We have concluded in previous research that professional mediation in online interventions is less preferred by informal dementia carers caring for longer ( Teles et al, 2020b ). In this study, the average duration of caregiving was of 6.1 (focus groups) and 4.1 (usability tests) years.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Concerning interaction with professionals in online interventions, participants in this study were perhaps more hesitant than what is usually reported in the literature ( Klein and Cook, 2010 ). We have concluded in previous research that professional mediation in online interventions is less preferred by informal dementia carers caring for longer ( Teles et al, 2020b ). In this study, the average duration of caregiving was of 6.1 (focus groups) and 4.1 (usability tests) years.…”
Section: Discussionmentioning
confidence: 88%
“…iSupport-Portugal is among the first culturally adapted versions of the program ( Teles et al, 2020a ). A five-step methodological approach was used to adapt iSupport to Portugal comprising: 1) needs assessment ( Teles et al, 2021 ; Teles et al, 2020b ); 2) content translation of the program by an authorized translator, and technical accuracy check of the translation by health and social support professionals; 3) cultural adaptation (semantic and conceptual equivalence of expressions, adaptation to cultural habits, traditions, local resources, and practices); 4) independent appraisal of contents by a panel of experts; and 5) fidelity check by WHO ( Teles et al, 2020a ).…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations